Aqueous extract from Madhuca indica bark protects cells from oxidative stress caused by electron beam radiation: in vitro, in vivo and in silico approach. Issue 5 (May 2019) - Vinutha, K.; Pavan, Gollapalli; Pattar, Sharath; Kumari, N Suchetha; Vidya, S.M.
Abstract: In an endeavor to find the novel natural radioprotector to secure normal cells surrounding cancerous cell during radiation exposure, Madhuca indica ( M. indica ) aqueous stem bark extract was evaluated for radioprotective activity using in vitro, in vivo, and in silico models. M. indica extract exhibited concentration dependent protective effect on electron beam radiation (EBR) induced damage to pBR322 DNA; the highest protection was achieved at 150 μg concentrations. Similarly, M. indica extract (400 mg/kg) administrated to mice prior to irradiation protected DNA from the radiation damage, which was confirmed by inhibiting comet parameters. The study showed a significant increase in the levels of glutathione and superoxide dismutase levels. The study also revealed that administration of M. Indica at the different dose to mice significantly reduced EBR induced MDA, sialic acid and nitric acid levels. Further extract prevented histophatological changes of skin and liver. In contrast, protein-protein interaction studies were performed to find the hub protein, involved in radiation-induced DNA damage. Among 437 proteins that are found expressed during radiation, p53 was found to be a master protein regulating the whole pathway. Molecular interaction between p53 and M. indica extract was predicted by quantitative structure-activity relationship and ADMET properties. Biomolecules such as quercetin, myricetin, and 7-hydroxyflavone were found to be promising inhibitors of p53 protein and may help in the protection of EBR induced DNA damage during cancer treatment.